2015
DOI: 10.3109/02656736.2015.1041430
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal stress triggered by near-infrared-irradiated carbon nanotubes up-regulates osteogenesis and mineral deposition in tooth-extracted sockets

Abstract: Our novel CNT-based PTS up-regulated osteogenesis via activation of heat shock-related molecules, resulting in promotion of mineral deposition in enhanced tooth-extracted sockets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…The results of cell viability experiments in the present study indicated that 45°C thermal treatment in vitro does not harm MC3T3 cells seriously, and stimulates ALP activity. Compared with the effects of osteogenesis in the previous study [42], those in the present study seemed to be weak. This is likely to be attributable to differences in temperature and the frequency of treatments between them.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of cell viability experiments in the present study indicated that 45°C thermal treatment in vitro does not harm MC3T3 cells seriously, and stimulates ALP activity. Compared with the effects of osteogenesis in the previous study [42], those in the present study seemed to be weak. This is likely to be attributable to differences in temperature and the frequency of treatments between them.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, Kajiya et al showed that everyday thermal treatment at 42°C for 10min. increased the activity of ALP in MC3T3 cells in a time-dependent manner compared with the non-thermal stress control [42]. Chen et al demonstrated the upregulated osteoblastic differentiation from MSCs with mild heat shock (41°C) [19].…”
Section: Discussionmentioning
confidence: 99%
“…4A), which suggested that 6 h at 5% 1 HZ stretch is the ideal condition to stimulate the osteogenic differentiation of BMSCs. Similar optimal force was also identified in photothermal stress-induced osteogenesis (37). These results will form the theoretical guidance for application during orthodontic tooth movement.…”
Section: Discussionsupporting
confidence: 67%
“…In the present study, severe hyperthermia alone significantly suppressed RUNX2 expression, which declined to near normal levels of control after combination with berberine. It is worth mentioning that thermal stress induces the expression of alkaline phosphatase, RUNX2 and Osx in mouse osteoblast MC3T3-E1 cells (19). Osx was upregulated in all groups.…”
Section: Discussionmentioning
confidence: 87%
“…Overall, the present study showed that hyperthermia may induce differentiation of osteosarcoma cells. Kajiya et al (19) reported that photothermal stress promotes mineral deposition in enhanced tooth-extracted sockets. On the other hand, it has been reported that berberine activates RUNX2 by p38 mitogen-activated protein kinase, leading to increased expression of osteogenic marker genes involving osteocalcin and osteopontin (20).…”
Section: Discussionmentioning
confidence: 99%